IMPLEMENTASI HYGIENE DAN SANITASI DALAM KITCHEN SHOW HOTEL INDIGO BALI SEMINYAK BEACH - Desak Ketut Dita Pramesti; Gede Yoga Kharisma Pradana (JISOS: JURNAL ILMU SOSIAL, 2022)
This article was produced based on research in order to analyze the principles of food hygiene & sanitation in the Hotel Indigo Bali. Hygiene & food sanitation are hygiene that are needed by hoteliers to make quality food. However, the food hygiene & sanitation in the show kitchen at Hotel Indigo Bali seems anomie in hospitality studies. The problem is centered on the hygiene & sanitation model in the Show Kitchen Hotel Indigo Bali. Problem solving is pursued based on the use of qualitative methods. Primary data were gathered through observation, interviews with informants at Hotel Indigo Bali Seminyak Beach. Secondary data were gathered entirely through a food sanitation literature review. All data was analyzed qualitatively with functional structural & symbol theory. The results showed that the principles of food hygiene & sanitation have become part of the standard operating procedures at Hotel Indigo Bali. The implementation of food hygiene & sanitation in the Show Kitchen Hotel Indigo Seminyak Beach looks different because there has been a structural violation in the practice of Show Kitchen Hotel Indigo Seminyak Beach. The creativity of actors in product presentation should care about cleanliness